The fundamentals of creative photography - Präkel, David (Another in the AVA academia series, 2010)
This guide offers an introduction to the world of applied creative photography. It explores the basic principles that underpin photography and guides the reader though the practical considerations involved in executing the perfect shot. The book is concerned with photography in a professional context.